Online representations of non-canonical sentences are more than good-enough. Issue 1 (January 2022) - Cutter, Michael G; Paterson, Kevin B; Filik, Ruth
Proponents of good-enough processing suggest that readers often (mis)interpret certain sentences using fast-and-frugal heuristics, such that for non-canonical sentences (e.g., The dog was bitten by the man ) people confuse the thematic roles of the nouns. We tested this theory by examining the effect of sentence canonicality on the reading of a follow-up sentence. In a self-paced reading study, 60 young and 60 older adults read an implausible sentence in either canonical (e.g., It was the peasant that executed the king ) or non-canonical form (e.g., It was the king that was executed by the peasant ), followed by a sentence that was implausible given a good-enough misinterpretation of the first sentence (e.g., Afterwards, the peasant rode back to the countryside ) or a sentence that was implausible given a correct interpretation of the first sentence (e.g., Afterwards, the king rode back to his castle ). We hypothesised that if non-canonical sentences are systematically misinterpreted, then sentence canonicality would differentially affect the reading of the two different follow-up types. Our data suggested that participants derived the same interpretations for canonical and non-canonical sentences, with no modulating effect of age group. Our findings suggest that readers do not derive an incorrect interpretation of non-canonical sentences during initial parsing, consistent with theories of misinterpretation effects that instead attribute these effects to post-interpretative processes.